Analysis of CD57+ natural killer cells and CD8+ T lymphocytes in periapical granulomas and radicular cysts - Luiz Arthur Barbosa da Silva; Maria Alice Ramalho Sá; Rafaela Albuquerque Melo; Joabe dos Santos Pereira; Éricka Janine Dantas da Silveira; Márcia Cristina da Costa Miguel (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: The aim of this study was to compare the number of CD57+ natural killer (NK) cells and CD8+ T lymphocytes between periapical granulomas (PGs) and radicular cysts (RCs). Twenty-fives cases of PGs and 25 of RCs were submitted to histological analysis and immunohistochemistry using anti-CD57 and anti-CD8 biomarkers. Positive cells were counted in 10 fields (400× magnification) and the median value was calculated for each case. Statistical tests were used to evaluate differences in the number of CD57+ NK cells and CD8+ T lymphocytes according to type of lesion, intensity of the infiltrate and thickness of the lining epithelium. The number of CD57+ NK cells and CD8+ T lymphocytes was higher in PGs than in RCs (p = 0.129 and p = 0.541, respectively). Comparison of the number of CD57+ NK cells in atrophic and hyperplastic epithelium revealed a larger number of cells in the atrophic epithelium (p = 0.042). A larger number of CD57+ NK cells and CD8+ T lymphocytes were observed in grade III infiltrates compared to grade I/II (p = 0.145 and p = 0.725, respectively). CD8+ T lymphocytes were more prevalent than CD57+ NK cells in most cases when PGs and RCs were analyzed separately or in combination (p < 0.0001). CD57+ NK cells and CD8+ T lymphocytes play a key role in antiviral defense and the presence of these cells supports evidence suggesting the participation of these microorganisms in the pathogenesis of PGs and RCs. The response mediated by CD8+ T lymphocytes was more frequent, indicating greater participation of the adaptive immunity in these chronic lesions.